2016
DOI: 10.1159/000445959
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Chronic Kidney Disease Progression: A Critical Review of the Evidence

Abstract: We performed a comprehensive literature review to examine evidence on the effects of hydration on the kidney. By reducing vasopressin secretion, increasing water intake may have a beneficial effect on renal function in patients with all forms of chronic kidney disease (CKD) and in those at risk of CKD. This potential benefit may be greater when the kidney is still able to concentrate urine (high fluid intake is contraindicated in dialysis-dependent patients). Increasing water intake is a well-accepted method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 90 publications
1
89
0
1
Order By: Relevance
“…Vasopressin may also contribute to CKD [9]. Following chronic administration of a vasopressin analogue to healthy rats, animals with normal kidneys develop renal hypertrophy [46] and albuminuria [10].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasopressin may also contribute to CKD [9]. Following chronic administration of a vasopressin analogue to healthy rats, animals with normal kidneys develop renal hypertrophy [46] and albuminuria [10].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Following chronic administration of a vasopressin analogue to healthy rats, animals with normal kidneys develop renal hypertrophy [46] and albuminuria [10]. Multiple mechanisms for vasopressin-induced renal damage have been proposed, such as glomerular hyperfiltration [9], activation of the renin-angiotensin-aldosterone system [47], and renal interstitial inflammation secondary to increased metabolic demand [48].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that increasing water intake in low-volume drinkers reduces copeptin levels in healthy adults [13,14] and decreases by 48% the recurrence of urinary tract infections [15]. Also, increasing water intake seems to benefit individuals of all stages of CKD or at risk of CKD [16].…”
Section: Introductionmentioning
confidence: 99%
“…Vanholder [30] pointed out the importance of primary prevention of CKD, demonstrating that it is more important than secondary prevention. Clark [31] et al reported the beneficial effects of increasing water intake on renal function in patients and those at risk of CKD, especially at the early stages of disease. Gulla et al [32] pointed out the necessity of timely referrals of patients with CKD, and of a system to promote them, because referrals were often made too late.…”
mentioning
confidence: 99%